Development of a 3D Solar System Learning Media Application Based on Augmented Reality - Rahmawati, Ardiani Putri; Novanti, Alya Nanda; Tirta, Muhammad Ihsan; Maisaroh, Lina; Nur Viranti, Risma Cahyani (Universitas Pendidikan Indonesia (UPI), 2024)
The present learning process is a unique challenge for teachers because the media created has to be creative, innovative, and not boring one of them on a 6th-thematic system learning material that USES book media as a learning tool. Students became less interested in studying these materials especially in today's era where society especially students coexist with technology. Interesting learning media is also essential for elementary school students. Teachers can use current learning media by taking advantage of technologies like augmented reality. Teachers can use the MBLC (multimedia development life cycle), which consists of six precepts, concept, design, collection of material, assembly, testing, testing, until distribution. Augmented reality is an application joining the real world with the virtual world in two and three dimensions projected in a real environment at the same time. Augmented reality can be used in entertainment, medicine, mechanics and learning media. Augmented reality can be built using the help of vuforia and unity 3d software. The end result of interactive learning media with augmented reality especially on solar system material that can later be created as a 3d image in an application.